Gemfibrozil Reduces Thrombin Generation in Patients with Combined Hyperlipidaemia, without Influencing Plasma Fibrinogen, Fibrin Gel Structure or Coagulation Factor VII - Bröijersén, Anders; Hamsten, Anders; Silveira, Angela; Fatah, Kamaran; Goodall, Alison H; Eriksson, Sabina; Angelin, Bo; Hjemdahl, Paul (Thrombosis and Haemostasis, 1996)
A double-blind, placebo-controlled, cross-over study was conducted in 21 men with combined hyperlipoproteinaemia to examine if lipid-lowering treatment with gemfibrozil (10-12 weeks) affects blood coagulation and fibrin gel structure at rest or during mental stress. Gemfibrozil lowered plasma triglycerides by 57 ± 4%, whereas high density lipoprotein (HDL) cholesterol increased by 22 ± 5%. Gemfibrozil lowered the triglyceride content of low density lipoprotein (LDL). Gemfibrozil reduced the plasma concentrations of thrombin-antithrombin complex (TAT) and prothrombin fragment F1+2 (F1+2), both at rest and during mental stress. However, there were no effects of gemfibrozil treatment on the plasma concentrations of fibrinogen, factor VII antigen, activated factor VII (Vila) or activated factor XII (XIIa), or on fibrin gel structure. Acute mental stress per se did not influence coagulation factors, reaction products or fibrin gel structure, or their responses to the study drug. Thus, gemfibrozil reduces thrombin generation in men with combined hyperlipoproteinaemia, without influencing the plasma levels of fibrinogen, Vila and XIIa, or fibrin gel structure. Attenuation of thrombin generation may contribute to the primary-preventive effects of gemfibrozil on coronary heart disease.